Bankruptcy Prediction Analysis in Goods Sector Companies Primary Consumers Listed on The Indonesia Stock Exchange - Nugraha, Maulana (Asosiasi Dosen Akuntansi Indonesia, 2022)
This study aims to determine there are differences in predicting the bankruptcy of primary consumer goods sector companies listed on the Indonesian stock exchange in 2016-2020 by using the Altman Zscore, Zmijewski and Springate bankruptcy prediction models in predicting corporate bankruptcy and to find out which prediction model is better. accurate in predicting corporate bankruptcy. The number of samples used in this study amounted to 18 companies with five years of observation and sampling technique using purposive sampling method. The data analysis technique used is the Kruskal-Wallis test and the level of accuracy test. The results of this study indicate that there is a significant difference from the results of the Altman Zscore, Zmijewski and Springate bankruptcy prediction models using the Kruskal-Wallish H test. with an accuracy rate of 78%.